A PORTRAIT OF MIND-MAPPING TECHNIQUE AND STUDENT PARTICIPATION IN WRITING ACTIVITY - Ida Lisdawati (JELA (Journal of English Language Teaching, Literature and Applied Linguistics), 2023)
The teacher must come up with an efficient, enjoyable, and simple way to boost students' writing activity. This study aims to describe the students' reactions with the help of mind mapping. Students in the eighth grade at a school in Cimahi, Indonesia, served as the study's subjects. The information gathered for the study was descriptive and qualitative. The outcomes revealed the answers from the pupils were favorable. In addition, the pupils struggled with sentence form and mechanics when producing recount texts. In addition, based on field notes, various challenges were encountered by the teacher during the teaching process, such as the low motivation of the pupils to complete the project. Therefore, it can be argued that using mind mapping can help students understand the subject and drive them to learn it.